The interaction between participatory leadership practices and perceived behavioral integrity and their impact on fighting deviant work behavior: An applied study on a sample of administrative leaders in private commercial banks in Sulaimani city in Iraq - Alhamdany, Saba Noori; Hussain, Wesam Ali; Alhamdany, Saad Noori; Hamed, Abdelsalam Adam (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to identify the extent to which private banks in the city of Sulaymaniyah adopt participatory leadership practices and perceived behavioral integrity, reveal the nature and direction of the relationship between participatory leadership and perceived behavioral integrity, and combat deviant behavior in these banks, in addition to determining whether the interaction is between participatory leadership and integrity. Perception affects the behavior of deviant work, and to achieve the objectives of the study, the researchers designed a questionnaire as a study tool that was distributed to the study sample of (108) managers, assistants of managers, heads of departments and divisions in private commercial banks in the city of Sulaymaniyah, and the results showed that private banks do not adopt participatory leadership practices and behavioral integrity Significantly, with a significant positive statistically significant effect of adopting participatory leadership practices on deviant work behavior in private banks in the city of Sulaymaniyah, where the value of the correlation coefficient R (-2.159) at the level of significance (.031), and the existence of a positive statistical significance effect. To adopt the perceived behavioral integrity on the deviant work behavior of private banks in the city of Sulaymaniyah, and the results revealed The study on the absence of a positive, statistically significant, positive impact at the level of (0.05) for the interaction between participatory leadership practices and perceived behavioral integrity on deviant work behavior. And their leaders, and emphasize the importance of adopting participatory leadership practices and perceived integrity together, as they have a clear impact on reducing deviant behaviors, which will positively affect banks in terms of creating a positive, effective and ideal work environment.